Isolation of Mesenchymal Stem Cells from Human Deciduous Teeth Pulp. (9th March 2017) - Tsai, Aileen I.; Hong, Hsiang-Hsi; Lin, Wey-Ran; Fu, Jen-Fen; Chang, Chih-Chun; Wang, I-Kuan; Huang, Wen-Hung; Weng, Cheng-Hao; Hsu, Ching-Wei; Yen, Tzung-Hai
Abstract : This study aimed to identify predictors of success rate of mesenchymal stem cell (MSC) isolation from human deciduous teeth pulp. A total of 161 deciduous teeth were extracted at the dental clinic of Chang Gung Memorial Hospital. The MSCs were isolated from dental pulps using a standard protocol. In total, 128 colonies of MSCs were obtained and the success rate was 79.5%. Compared to teeth not yielding MSCs successfully, those successfully yielding MSCs were found to have less severe dental caries (no/mild-to-moderate/severe: 63.3/24.2/12.5% versus 12.5/42.4/42.4%, P < 0.001 ) and less frequent pulpitis (no/yes: 95.3/4.7% versus 51.5/48.5%, P < 0.001 ). In a multivariate regression model, it was confirmed that the absence of dental caries (OR = 4.741, 95% CI = 1.564–14.371, P = 0.006 ) and pulpitis (OR = 9.111, 95% CI = 2.921–28.420, P < 0.001 ) was significant determinants of the successful procurement of MSCs. MSCs derived from pulps with pulpitis expressed longer colony doubling time than pulps without pulpitis. Furthermore, there were higher expressions of proinflammatory cytokines, interleukin- (IL-) 6 and monocyte chemoattractant protein- (MCP-) 1, P < 0.01, and innate immune response [toll-like receptor 1 (TLR1) and TLR8, P < 0.05 ; TLR2, TLR3, and TLR6, P < 0.01 ] in the inflamed than noninflamed pulps. Therefore, a carious deciduous tooth or tooth with pulpitis was relatively unsuitable for MSC processing and isolation.